PENGARUH DIMENSI FRAUD DIAMOND DAN RELIGIUSITAS TERHADAP KECURANGAN AKADEMIK - Ni Putu Ayu Yuniari; Sang Ayu Putu Arie Indraswarawati; Cok. Gde Bayu Putra (UNHI Press, 2021)
This study aims to determine the effect of diamond fraud and religiosity on academic fraud in accounting students of the University of Hindu Indonesia . This research was conducted at the University of Hindu Indonesia. The number of samples taken was 172 students with a probability sampling method. Data collection was carried out by distributing questionnaires. The analysis technique used is multiple linear regression. The results showed that pressure has a significant effect on academic fraud y ang means that the pressure received by students triggers students to commit academic fraud. Ability has a significant effect on academic fraud, which means that the higher the student's ability to commit cheating, the higher the cheating is committed. Religiosity has a significant effect on academic fraud, which means that the higher the level of religiosity, the more students understand that in religion there is a punishment in the hereafter for doing bad things. Opportunity and rationalization do not have a significant effect, which means that opportunity and rationalization do not influence students to commit academic fraud.